2020
DOI: 10.1002/pip.3364
|View full text |Cite
|
Sign up to set email alerts
|

Defect engineering in cast mono‐like silicon: A review

Abstract: Cast mono‐like silicon is a promising material for next‐generation silicon solar cells with higher efficiency and lower cost compared with currently commercialized silicon solar cells. So far, cast mono‐like silicon technique still faces several problems, including multicrystallization, dislocation clusters, sub‐grain boundaries, and impurity contamination, which hinder its mass‐scale applications in photovoltaic industry. In this review, we will introduce these common problems in turn and discuss a multitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 86 publications
(174 reference statements)
1
15
0
Order By: Relevance
“…The bottom and top parts of the ingot usually contain high concentrations of impurities due to their diffusion from the crucible walls and the segregation effect during the casting process 43 . As expected, the un‐gettered bottom wafers show an inferior performance with global i V OC below 540 mV.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…The bottom and top parts of the ingot usually contain high concentrations of impurities due to their diffusion from the crucible walls and the segregation effect during the casting process 43 . As expected, the un‐gettered bottom wafers show an inferior performance with global i V OC below 540 mV.…”
Section: Resultssupporting
confidence: 53%
“…The dark line‐shaped patterns in the i V OC images (Figure 1A–D) are caused by crystallographic defects. EBSD measurements (see Figure A1) confirmed that those features are low angle grain boundaries, which are normally formed due to the movement and aggregation of a high density of dislocations 42,43 . The residual stress and strain around these dislocations can naturally capture other defects and impurities, and thus, make these regions highly recombination active 44 .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Recently, a rapid developing technology, namely, cast-monosilicon (cm-Si), has taken a certain market share. [1] Due to the development of a proper seed arrangement and the use of functional grain boundary technology, the propagation of dislocations in cm-Si could be effectively suppressed, [2,3] resulting in the conversion efficiency of cm-Si passivated emitter rear contact (PERC) solar cells exceeding 23%. In addition, the growth process of cm-Si is fully compatible with that of mc-Si, which is suitable for mass production.Light-and elevated-temperature-induced degradation (LeTID) is a significant problem in PERC solar cells.…”
mentioning
confidence: 99%
“… 4 However, the bottom red zone because of the metal contamination and the high dislocation region at the top of the ingot are still the practical drawbacks, which limited its competitiveness to the monocrystalline Si grown by the Czochralski method. 5 Crystal structures and properties of the mono-like DS-Si ingots depend on the seed arrangement, growth interface evolution, generation and propagation of dislocations, thermal stress relaxation, impurity transport, etc. Especially, the high dislocation density gives negative influence on the conversion efficiency of solar cells by providing not only recombination sites for minority carriers but also shunt regions for majority carriers.…”
Section: Introductionmentioning
confidence: 99%